How Spain Reached 40 Deceased Organ Donors per Million Population. Issue 6 (9th January 2017) - Matesanz, R.; Domínguez‐Gil, B.; Coll, E.; Mahíllo, B.; Marazuela, R.
Abstract : With 40 donors and more than 100 transplant procedures per million population in 2015, Spain holds a privileged position worldwide in providing transplant services to its patient population. The Spanish success derives from a specific organizational approach to ensure the systematic identification of opportunities for organ donation and their transition to actual donation and to promote public support for the donation of organs after death. The Spanish results are to be highlighted in the context of the dramatic decline in the incidence of brain death and the changes in end‐of‐life care practices in the country since the beginning of the century. This prompted the system to conceive the 40 donors per million population plan, with three specific objectives: (i) promoting the identification and early referral of possible organ donors from outside of the intensive care unit to consider elective non‐therapeutic intensive care and incorporate the option of organ donation into end‐of‐life care; (ii) facilitating the use of organs from expanded criteria and non–standard risk donors; and (iii) developing the framework for the practice of donation after circulatory death. This article describes the actions undertaken and their impact on donation and transplantation activities. Abstract : The authors summarize the challenges that the Spanish donation and transplantation system has faced in further developing deceased organ donation, and describe the three strategies that allowed Spain to rise to the highest solid organ transplant activity in the world in 2015. For further discussion, see the letters from Sharif (page 1694 ) and Matesanz (page 1695 ).